2022
DOI: 10.3389/fcell.2022.873319
|View full text |Cite
|
Sign up to set email alerts
|

Role of an Exosomes-Related lncRNAs Signature in Tumor Immune Microenvironment of Gastric Cancer

Abstract: Background: Exosomes plays a crucial role in intercellular communication of gastric cancer (GC), while long non-coding RNAs (lncRNAs) contributes to the tumorigenesis and progression of GC. This study aims to explore the prognostic exosomes-related lncRNAs of GC patients.Methods: Data of 375 GC patients were obtained from the TCGA database. The entire cohort was randomly divided into a training cohort and a validation cohort in a 2:1 ratio. Exosomes-related lncRNAs were identified by the Pearson correlation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In fact, many prognostic and predictive signatures for tumor patients based on exosome-related processes have been developed ( Wu et al, 2021 ; Li et al, 2022 ; Lin et al, 2022 ; Wu et al, 2022 ). But, taking only exosome-related processes into consideration may not be enough.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, many prognostic and predictive signatures for tumor patients based on exosome-related processes have been developed ( Wu et al, 2021 ; Li et al, 2022 ; Lin et al, 2022 ; Wu et al, 2022 ). But, taking only exosome-related processes into consideration may not be enough.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study also revealed that lncRNA NORAD knockdown induces the secretion of exosomes containing miR-199a-5p to suppress the ubiquitination of PD-L1 in an ESCC mouse model, resulting in enhanced efficacy of anti-PD-1 in combination with radiation [122]. In addition, Li et al also identified that B7-H3 and VSIR might be novel checkpoints for their upregulated expression in GC patients, affecting the efficacy of immunotherapy [123]. These results indicate that the application of immune checkpoint inhibitors or antibodies aiming to interfere with exosomal lncRNA-mediated checkpoint interaction benefits the normal function of immune cells, thereby improving the efficacy of cancer treatment.…”
Section: Exosomal Lncrna-based Cancer Treatmentmentioning
confidence: 98%
“…Recent advancements in cancer prognostics underscore the pivotal role of exosomes in tumor microenvironment modulation across various cancers [ [23] , [24] , [25] , [26] , [27] , [28] , [29] ]. Studies, including groundbreaking work on head-neck squamous cell carcinoma [ 30 ], have elucidated the prognostic significance of exosome-related genes (ERGs) in forecasting treatment responses and patient prognoses.…”
Section: Introductionmentioning
confidence: 99%